Sistem Pakar Diagnosa Kerusakan Hardware Komputer Menggunakan Metode Forward Chaining dan Certainty Factor Berbasis Website - Oka Saputra; Iskandar Fitri; Endah Tri Esti Handayani (KITA Institute, 2022)
Computers have become a huge requirement to support human performance. Computers also often experience Hardware damage such as processors, VGA, motherboards, memory, mouse, keyboards, hard disks, optical drives, monitors. Until now, many computer users still do not have sufficient knowledge of the initial diagnosis of computer Hardware damage which causes a lot of computer users to pay a lot of money to find out and repair the damage that occurs to Computer Hardware. In this Expert System application research development, the authors use a combination of two inference methods, namely the Forward Chaining method and the Certainty Factor Method. The programming tools used in the development of this Expert System application is using the Sublime Text 3 application while the database uses MySQL with PHP as the programming language. The purpose of this Expert System application is made to assist computer users in making an initial diagnosis of a damaged computer Hardware along with the causes and solutions to overcome the damage.